KERANGKA HUKUM UNTUK KERJASAMA PUBLIK-SWASTA (PPS) DALAM SEKTOR INFRASTRUKTUR: PERSPEKTIF INDONESIA - Dwiyanti utami; Suyatno (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Strong legal framework for public-private partnerships (PPP) in Indonesia's infrastructure sector is critical to increasing private investment and increasing cost efficiency. PPP can help increase community participation in public service delivery and increase transparency in public service delivery. In recent years, the Indonesian government has attempted to increase investment and infrastructure development through collaboration with the private sector. However, this collaboration also has several challenges, including differences in interests and culture between the government and the private sector. Therefore, it is necessary to create a clear and effective legal framework to regulate PPS cooperation. This article discusses the importance of a strong legal framework for PPS cooperation in the infrastructure sector in Indonesia and its impact on sustainable economic growth and reliable energy supply for society